Laparoscopic Inguinal Hernia Repair; Comparison between the Major Techniques: TEP and TAPP - Elhaj Abdelkarem, Mohamed Elfatih Mohamed (Gezira Journal of Health Sciences, 2014)
Introduction: Laparoscopic inguinal hernia repair made an important revolutionary stage in hernia management and with the accumulative knowledge and experience it is becoming the gold standard way of inguinal hernia repair. The choice of approach to the laparoscopic repair of inguinal hernia is controversial. There is a scarcity of data comparing the laparoscopic transabdominal preperitoneal (TAPP) approach with the laparoscopic totally extraperitoneal (TEP) approach and questions remain about their relative merits and risks.